Preparation and photocatalytic performance of the rod-shaped Ni-NiO/TiO2 hollow composite structure based on metallization cellulose fibers and TBOT. (January 2019) - Pan, Yanfei; Liu, Bo; Hu, Huixiang; Jiang, Haodong; Wei, Feng; Zhou, Min; Fan, Xinyan; Yu, Haibiao; Niu, Gengwu; Huang, Jintian
Abstract: The rod-shaped Ni-NiO/TiO2 hollow composite structure based on metallization cellulose fibers and Titanium butoxide (TBOT) via Sol-Gel method was fabricated to obtain a highly active rod-shaped hollow catalysts. The results showed that the high-heat treatment had no obvious influence on the hollow structure cavity size and the ideal surface roughness value of hollow structure was 6.385 μm. The XRD patterns revealed that the Ni and TiO2 particles that had been deposited on cellulose fibers had a crystallite size structure between 16.5 and 19.4 nm. The characteristic absorption peak at 1035 cm −1 assigned to Ti-O-C of anatase nano-TiO2 on hollow structure surface appeared. It is feasible to control the crystallite size and hollow cavity pore size via Sol-Gel method. The magnetic hollow structure shown here can be applied as catalysts and it can be completely natural subsidence within 5 min. Herein, the catalytic capacity of the rod-shaped Ni-NiO/TiO2 hollow composite structure for Cu (II) was found to be 5696 mg g −1 . Highlights: It is reasonable and feasible to prepare the hollow composite structure via electroless Ni and Sol-Gel method. The characteristic absorption peak of anatase nano-TiO2 at 1035 cm −1 assigned to Ti-O-C appeared. The catalytic amount of samples without grinding was up to 5696 mg/g. The photocatalytic activity barely decreased via 5 cycles and the Ni-NiO/TiO2 hollow composite structure can settle completely in 5 min. The ideal Ra (Ra illustrated Line Roughness) value of hollow structure was 6.385 μm.